Relationship of Family Income and Family Support with Maternal Reference in Pregnant Women in Pantai Cermin BEmONC, Langkat District, 2019 - Siti Maryam Hsb; Heru Santosa; Asfriyati Asfriyati (Budapest International Research and Critics University, 2020)
Basic emergency obstetric and newborn care (BEmONC) is an inpatient Publlich Health Center that is able to provide obstetric and neonatal emergency/ basic complications services 24 hours a day and 7 days a week. In Public Health Center the referral service ideally is no more than 15%, the high number of maternal referrals in BEMONC Pantai Cermin Langkat District exceeds the Standard (> 15%). The number of maternal referrals in pregnant women starting from 1 May 2018 to 31 October 2018 was 104 people. Factors related to maternal referral to pregnant women in Pantai Cermin BEmONC, Langkat district are maternal knowledge, and support of health workers. The purpose of this study was to determine the relationship of maternal knowledge, and support of he alth workers with the maternal referral process in pregnant women. This study used a cross sectional design, with 104 pregnant women being referred at Pantai Cermin BEmONC, Langkat district by method of total sampling. Data collection methods consist of primary data and secondary data. Based on the results of the study note that out of 104 respondents there were 54 (51.9%) maternal referral processes in incompatible pregnant women and 50 (48.1%) maternal referral processes in pregnant women in accordance with the reference standard. Variables related to the maternal referral process in pregnant women were family income (p = 0.049), and family support (p = 0.028).There is a relationship between family income and family support with the maternal referral process for pregnant women at the BEMONC Public Health Center Pantai Cermin Langkat Regency.